2023
DOI: 10.1093/asjof/ojad002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Implication of Social Media Platforms on Plastic Cosmetic Surgery: A Cross-sectional Study in Saudi Arabia From 2021 to 2022

Abstract: Background Aesthetic procedures are considered one of the most commonly performed procedures in the medical field. Social media (SM) reflects the electronic platforms that deliver an enormous amount of information to different users and enable them to share their content and experience with others at the simple click of a button. In our modern era, SM platforms affect different angles of our lives, from a simple detail to a significant complex aspect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Social media plays a large role in dissemination of medical information and increasing population awareness while allowing for patients to share their experiences. However, monitoring the accuracy of information shared in online forums remains a significant challenge 25–30 . Unanimously, participants in this study first learned about RCPD online, via online social media platforms such as Reddit®, Facebook®, TikTok®, and YouTube®, which is consistent with other studies published 11 .…”
Section: Discussionsupporting
confidence: 81%
“…Social media plays a large role in dissemination of medical information and increasing population awareness while allowing for patients to share their experiences. However, monitoring the accuracy of information shared in online forums remains a significant challenge 25–30 . Unanimously, participants in this study first learned about RCPD online, via online social media platforms such as Reddit®, Facebook®, TikTok®, and YouTube®, which is consistent with other studies published 11 .…”
Section: Discussionsupporting
confidence: 81%
“…9 Al Bahlal et al found that surgeons' advertisements affected the decision of 35.9% of their participants to seek cosmetic consultations. 32 Other than social media exposure or medical professionals and in uencers, having a family member or a friend who have undergone facial llers or Botox encouraged more individual into opting for such procedures (p value = 0), as they can be a source of information, vicarious experience as well as motivation. [33][34][35] Arab et al showed that having a family member or a friend who had undergone facial injections in uenced more individuals when exposed to cosmetic treatment ads on social media.…”
Section: Discussionmentioning
confidence: 99%
“…While social media provides a novel opportunity for community and information sharing, challenges exist when sharing medical information online [43]. Monitoring the accuracy of information shared remains a significant hurdle that is yet to be solved [44][45][46][47][48][49]. The RCPD online community has a significant following, with the Reddit ® page 'r/noburp' reporting over 22,000 subscribers and close to 5000 new members in the last year alone [42].…”
Section: The Role Of Social Mediamentioning
confidence: 99%